2015
DOI: 10.12688/f1000research.6641.1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Prevalence of Coronary Artery Disease in Adult Patients with Cardiac Myxomas

Abstract: Background: Studies have reported varied prevalence estimates of coronary artery disease (CAD) in cardiac myxoma patients. We performed a systematic review and meta-analysis of observational studies to summarize the point prevalence of CAD in adults with cardiac myxomas. Methods and Results: Two independent investigators searched MEDLINE and LILACS databases using the terms " Myxoma”, " Coronary Angiography" and " Coronary Disease" from inception through December 2014 for all relevant studies. We included 6 ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Mean age at diagnosis is 50 years, and approximately 70% occur in women [ 74 ]. When occurs in syndromic context, more common in young males, has a multifocal development with multisite origin [ 75 ].…”
Section: Myxomamentioning
confidence: 99%
“…Mean age at diagnosis is 50 years, and approximately 70% occur in women [ 74 ]. When occurs in syndromic context, more common in young males, has a multifocal development with multisite origin [ 75 ].…”
Section: Myxomamentioning
confidence: 99%
“…A systematic review and meta-analysis of 109 patients with cardiac myxoma by Silva et al showed a CAD prevalence ranging from 5.3% to 36.3% with an average of 20.7%. 9 Patients with myxoma can present with constitutional symptoms, dyspnoea, angina, syncope or embolic manifestations. In addition, myxomas can present as myocardial infarction secondary to arterial embolisation.…”
Section: Descriptionmentioning
confidence: 99%
“…Erdil et al found a 36% prevalence rate of CAD2 whereas Fueredi et al 7 and Velasco et al 8 reporting a higher prevalence (66.7% and 82%, respectively). A systematic review and meta-analysis of 109 patients with cardiac myxoma by Silva et al showed a CAD prevalence ranging from 5.3% to 36.3% with an average of 20.7% 9. Patients with myxoma can present with constitutional symptoms, dyspnoea, angina, syncope or embolic manifestations.…”
Section: Descriptionmentioning
confidence: 99%
“…Although extremely rare, myxomas are the most common cardiac tumors, accounting for more than 50% of all cases worldwide. 1 , 2 Despite being histologically benign, myxomas can have a wide spectrum of presentations based on their anatomic location, size, and mobility. They can mimic various heart conditions and present as cardiac insufficiency, valvular heart disease, syncope, peripheral embolic events, and systemic symptoms.…”
Section: Introductionmentioning
confidence: 99%